Bisnis Peralatan Sembahyang Ditinjau Dari Etika Kristen - Daniel Sidianto; Yanto Paulus Hermanto; Julia Tanama (Sekolah Tinggi Teologi Arastamar Bengkulu, 2022)
There are several business sectors that disturb the tranquility of Christian life, types of business: producers of prayer paper, producers of hio or incense to hold ritual worship of gods, the making of statues of gods of worship. If the businessman is a non-Christian then it will certainly not cause problems, but if the businessman is a Christian then bring him into a dilemmatic state. What is the attitude of Christians towards life for this business of prayer equipment. First, it is indicated the problem of how the character of Christian businessmen is viewed from Christian Ethics. Christian business ethics in highlighting all business activities of Christians, including the production of prayer equipment should also be reviewed from the basis of devotion. The basis of devotion from biblical excavation in the context of devotion to mammon or to God is the basis for important considerations for Christians in conducting these business activities. Second, it is indicated that the problem of whether the business engaged in by Christians who produce prayer equipment fulfills the Great Commission of the Lord Jesus. The business of prayer equipment if it is a contextualization of the gospel into the business area that is a means of preaching the gospel, it will be a separate consideration, because in the business the prayer equipment becomes a forum for the implementation of the great Commission. Which resulted in the conclusion of the study answering the study regarding the title of this study.